Study of Production-Injection Strategies for Sustainable Production in Geothermal Reservoir Two-Phase by Numerical Simulation - Pratama, Heru Berian; Saptadji, Nenny Miryani (Geological Agency, 2021)
DOI: 10.17014/ijog.8.1.25-38The rapid pressure decline in liquid-dominated geothermal fields is a significant problem affecting the steam supply to the power plant. This study aims to understand the reservoir characteristics changes due to extraction of mass and heat from the reservoir through a numerical reservoir simulation under various strategies production-injection. The development of a liquid-dominated geothermal field model is assessed with various production strategies and injection strategies for the generation of 110 MW and 220 MW using a separated steam cycle. Thirty two production-injection strategies from a full factorial have been successfully carried out. The results show a low decrease for both reservoir pressure and decline rate for the steam cap and brine reservoir's production strategy combined with deep and dispersed injection strategy. From a simulation for 220 MW, the strategy for sustainable production is 25% from the steam cap and 75% from brine reservoir, dispersed, and deep reinjection with 9 make-up wells from the steam cap. The lowest decline rate after the 30th year is 0.5%, with Arps 1.0 exponent harmonic decline curve. The implementation of the production-injection strategy needs to be planned from the beginning of exploration or exploitation so that the strategy can be adjusted to changes in reservoir characteristics without causing problems.